Methodology of ECG Interpretation in the Nagoya Program - Okajima, M.; Okamoto, N.; Yokoi, M.; Iwatsuka, T.; Ohsawa, N. (Methods of Information in Medicine, 1990)
The outline of the Nagoya Program, the most representative software package for computerized electrocardiography in Japan, is described. First, the history and current status of research and its transfer to commercial products for computerized interpretation of electrocardiograms is briefly reviewed. Second, development and testing of the Nagoya Program is depicted, referring to a gold standard for evaluation and the database being used for this purpose, and to its participation in the CSE study. Third, a description of signal acquisition and wave identification is given, followed by the detection of rhythm disturbances. Next, algorithms for contour classification, which consist of decision-tree logic established through trial and error and making use of the database of ECGs, are described. Finally, special features and future plans of the Nagoya Program are mentioned.
Keywords: ECG Database; Algorithm; Decision Trees; Point Scoring; Japanese Population